Mechanisms for development in corporate citizenship: A multi-level review - Fred Ogola; Josep Francesc Mària i Serrano (International Journal of Corporate Social Responsibility (JCSR), 2020)
Social Responsibility, referred to in this study as Corporate Citizenship (CC) has experienced continued growth in significance among academics and corporate leaders. The absence of a multi-level approach to what would explain the advancement in CC has inhibited a realization of singularly conclusive study. In fact, nearly every scholar in the field of CC has come up with their perspective to explain the mechanisms for development in corporate citizenship, none of them being singularly conclusive. This study takes multi-level review of the current body of knowledge on mechanisms for development in corporate citizenship. This is achieved through a comprehensive synthesis of the literature around the mechanisms for development in CC from a multi-level perspective. The findings show that the majority of scholars still populate disciplinary, specialized micro- (Managerial values), meso- (Business Case) or macro- (Institutional Mechanisms) as a driver for the development of CC. we also found out that previous studies that have explored to explain drivers for CC either falls under the Managerial values, business case, or Institutional mechanisms. The findings also indicate that none of the singular perspectives have explained development in CC with conclusive results. Further the study demonstrates that it is the interaction between the different three levels of mechanisms for CC development (BC, MVs and IMs), but not acting separately is what could be driving CC to another level. Finally this study, recommends a multi-level approach to the study in social responsibility.
Keywords: 650; Corporate social responsibility; Corporate citizenship; Drivers for corporate citizenship; Business case; Managerial values; Institutional mechanisms; Multilevel perspectives